The Influence of Social Media in Promoting Knowledge Acquisition and Pathology Excellence in Nigeria - Folaranmi, Olaleke Oluwasegun; Ibiyeye, Kehinde Muibat; Odetunde, Olabode Ali; Kerr, Darcy A. (Frontiers in Medicine, 2022)
The use of social media has evolved from platforms designed primarily for social connection and news sharing to include vibrant virtual academic environments. These platforms allow pathologists from across the globe to interact, exchange knowledge, and collaborate. Pathology in Nigeria, as in much of Africa, faces severe knowledge and practice gaps, with a lack of supporting modern laboratory infrastructure. Social media represents a potentially highly valuable avenue to help address some of these deficiencies. In this Perspective piece, we highlight our experience with the increasing role of social media in providing quality medical education in pathology globally, with an emphasis on how it bridges many of these gaps in Nigeria. Social media sites serve as sources of readily accessible, free, high-quality information to pathologists and trainees through academic discussions, quizzes, journal clubs, and also opportunities for professional networking and research collaborations. Despite the availability and wide reach of these platforms, social media as a tool for advancement of knowledge in pathology is still undersubscribed in this part of the world. Improving awareness of and support for these tools will ideally help mitigate some of the challenges of practicing pathology in low and middle-income settings.